Elite athletes travelling to international destinations >5 time zone differences from their home country have a 2-3-fold increased risk of illness - Schwellnus, M. P.; Derman, W. E.; Jordaan, E.; Page, T.; Lambert, M. I.; Readhead, C.; Roberts, C.; Kohler, R.; Collins, R.; Kara, S.; Morris, M. I.; Strauss, O.; et al. (British Journal of Sports Medicine, 2012)
Background: Illness accounts for a significant proportion of consultations with a team physician travelling with elite athletes. Objective To determine if international travel increases the incidence of illness in rugby union players participating in a 16-week tournament.Setting 2010 Super 14 Rugby Union tournament. Participants: 259 elite rugby players from eight teams were followed daily over the 16-week competition period (22 676 player-days). Assessment: Team physicians completed a logbook detailing the daily squad size and illness in any player (system affected, final diagnosis, type and onset of symptoms, training/match days lost and suspected cause) with 100% compliance. Time periods during the tournament were divided as follows: located and playing in the home country before travelling (baseline), located and playing abroad in countries >5 h time zone difference (travel) and located back in the home country following international travel (return).Main outcome measurement Incidence of illness (illness per 1000 player-days) during baseline, travel and return. Results: The overall incidence of illness in the cohort was 20.7 (95% CI 18.5 to 23.1). For all teams, the incidence of illness according to location and travelling was significantly higher in the time period following international travel (32.6; 95% CI 19.6 to 53.5) compared with the baseline (15.4; 95% CI 8.7 to 27.0) or after returning to their home country (10.6; 95% CI 6.1 to 18.2). Conclusions: There is a higher incidence of illness in athletes following international travel to a foreign country that is >5 h time difference and this returns to baseline on return to the home country.